Analisis Pengaruh Suhu terhadap Perkembangan Penyakit Bercak Daun (Cercospora sp.) pada Tanaman Edamame (Glycine max L. Merr.) di Institut Teknologi Sawit Indonesia - Anri Arjuna Simbolon; Guntoro Guntoro (Lembaga Teewan Journal Solutions, 2026)
This study aimed to determine the effect of temperature and number of conidia on the severity of leaf spot disease caused by Cercospora sp. on edamame plants. The study was conducted from April 16 to May 30, 2026, by observing environmental temperature, the number of conidia captured using spore traps, and the severity and incidence of the disease in edamame plants. The results showed that the temperature during the observation was relatively stable in the range of 29.7–31.3°C with an average of 30.55°C, while the number of conidia increased from 10 conidia at the beginning of the observation to 39 conidia at the end of the observation. The severity of the disease also increased from 0.02 to 0.60, while the incidence of the disease increased from 65.0% to 100% in early May 2026. The results of multiple linear regression analysis showed that temperature had no significant effect partially on disease intensity, while the number of conidia had a significant and more dominant effect in increasing disease severity. Simultaneously, temperature and the number of conidia significantly influenced the disease intensity with an R Square value of 0.567. Thus, the number of conidia is the main factor influencing the development of Cercospora sp. leaf spot disease in edamame plants.